1993
DOI: 10.1007/bf01213345
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of lipid metabolism in children with chronic renal failure

Abstract: This review discusses the pathogenesis, clinical significance and current therapy of hyperlipoproteinaemia (HLP) in children with chronic renal failure. Uraemic dyslipidaemia, characterized by hypertriglyceridaemia and low high-density lipoprotein-cholesterol levels, is present in the majority patients with chronic renal failure. In addition, serum levels of total cholesterol, very low-density lipoprotein-cholesterol, low-density lipoportein-cholesterol and apolipoprotein B are frequently elevated. The pathoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 85 publications
4
27
1
Order By: Relevance
“…Disturbances of lipid metabolism in children with chronic renal failure had been reviewed by Querfeld in 1993 [4]. He reported that uremic dyslipidemia characterised by high TGD and low HDL-C serum levels was present in the majority of patients whereas levels of TC, LDL-C and VLDL-C were frequently elevated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbances of lipid metabolism in children with chronic renal failure had been reviewed by Querfeld in 1993 [4]. He reported that uremic dyslipidemia characterised by high TGD and low HDL-C serum levels was present in the majority of patients whereas levels of TC, LDL-C and VLDL-C were frequently elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemias are disorders of lipoprotein metabolism that result in excess total cholesterol (TC), excess low-density lipoprotein cholesterol (LDL-C), excess triglyceride (TGD), or deficiency of high-density lipoprotein cholesterol (HDL-C). Dyslipidemia patterns similar to familial hypertriglyceridemia or type IV hyperlipidemia were found to be common in pediatric patients undergoing chronic dialysis treatment [1][2][3][4]. There are many factors which may contribute to the risk of dyslipidemia in chronic dialysis patients, such as a diet rich in fat and carbohydrates [1], medications [5], use of high molecular weight heparin [6], decrease in lipoprotein lipase level [1], high glucose content of dialysate [7] and L-carnitine deficiency [1].…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of hyperlipidemia is known to be different in uremic children according to the mode of renal replacement therapy before transplantation and, after transplantation, the pattern of hyperlipidemia rapidly changes during the first few months [4]. It has been shown in the adult population that, regardless of the type of hyperlipidemia prior to renal transplantation, the serum lipid pattern converges to a new, common pattern of "post-transplant hyperlipidemia" [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The data are more alarming for young CKD patients, as CVD-specific mortality rates in children and young adults with ESRD have increased over the last two decades (3) and are approximately 1000 times higher than in comparably aged populations without CKD (4). It is likely that the coexistence of highly prevalent traditional (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and uremia-related (16 -19) cardiovascular risk factors (CVRF) contribute to this population's unique susceptibility to CVD.…”
Section: Introductionmentioning
confidence: 99%